2020
DOI: 10.33448/rsd-v9i12.10896
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of beet dye (Beta vulgaris L.) using maltodextrin and xanthan gum as encapsulant agents and application in yogurt

Abstract: Beet is a vegetable rich in antioxidant activity and phenolic compounds, besides being used as a natural dye, which has as a disadvantage the instability in relation to several factors, such as temperature, pH, oxygen and light. Therefore, this work aimed to microencapsulate the beet dye, evaluate the stability of powders and their application in yogurt. Beet extract was encapsulated in a combination of maltodextrin and xanthan gum, with subsequent drying in spray dryer or lyophilizer. In the powders obtained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
1
1
3
Order By: Relevance
“…When comparing the presence and absence of light during storage at 25 °C, concentrations decreased in both cases for TA (14.17% with light and 12.78% without light) and TP (17.92% with light and 12.06% without light). The TP was more degraded than the TA, indicating that the presence of light influenced the degradation of this group of compounds, as already reported elsewhere [ 4 , 16 , 23 ]. Burin et al [ 25 ] studied the effects of temperature and exposure to light on the stability of anthocyanins from Cabernet Sauvignon, and their results also revealed that light is a significant factor in accelerating the degradation of anthocyanins.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…When comparing the presence and absence of light during storage at 25 °C, concentrations decreased in both cases for TA (14.17% with light and 12.78% without light) and TP (17.92% with light and 12.06% without light). The TP was more degraded than the TA, indicating that the presence of light influenced the degradation of this group of compounds, as already reported elsewhere [ 4 , 16 , 23 ]. Burin et al [ 25 ] studied the effects of temperature and exposure to light on the stability of anthocyanins from Cabernet Sauvignon, and their results also revealed that light is a significant factor in accelerating the degradation of anthocyanins.…”
Section: Resultssupporting
confidence: 82%
“…The EE for the MD/GX was 68.10%. These results were better than those observed by Antigo et al [ 16 ], who obtained an EE of 43.45% using beet extract and encapsulation via lyophilization with MD/GX. The study by Mahdavi et al [ 17 ], using barberry extract and encapsulation via spray drying with three different wall materials—that is, combining maltodextrin, gum arabic, maltodextrin, and gelatin—obtained higher values (ranging from 89.06 to 96.21%) when compared with the ones observed in the present study.…”
Section: Resultscontrasting
confidence: 75%
“…A acidez titulável do leite fermentado pelas duas cepas apresentou significativamente superior comparado ao somente fermentado por L. helveticus. Antigo et al (2020) desenvolveu iogurte fermentado por Lactobacillus acidophilus, Bifidobacterium animalis subsp. lactis e S. thermophilus adicionado de corante de beterraba apresentou acidez médio de 0,8% de ácido lático/100 g. O leite fermentado por L. helveticus e S. thermophilus apresentaram contagem superior ao fermentado somente por L. helveticus.…”
Section: Análises Microbiológicasunclassified
“…O tipo, concentração e propriedades do material capsular afetam marcadamente a viabilidade dos probióticos encapsulados. Inúmeros biomateriais, incluindo carboidratos (lactose, maltodextrina, alginato, amido, amidos modificados e sacarose), lipídios (monoglicerídeos, diglicéridos e óleos hidrogenados) e proteínas (caseína, proteínas do soro do leite, gelatina e albumina) já foram estudados e mostram-se com potencial para serem utilizados no encapsulamento de probióticos, e, além destes outros podem ser usados desde que satisfaçam aos requisitos dos materiais geralmente reconhecidos como seguros (status GRAS) (Abd El-Salam & El-Shibiny, 2015; Antigo et al, 2020;Santos et al, 2014). Segundo Dianawati; Mishra; Shah (2015) vários materiais de encapsulamento preparados a partir de carboidratos (álcoois de açúcar, açúcares, polissacarídeos, hidrocoloides) ou proteínas (à base de leite ou não) ou diversas combinações têm sido estudados, para verificar sua eficácia na proteção de bactérias probióticas.…”
Section: Principais Agentes Encapsulantes Estudadosunclassified